Analisis Karakteristik Geokimia Batuan Potensi Pembentuk Air Asam Tambang Daerah Tanjung Kabupaten Bone - Firman Nullah Yusuf; Andi Fahdli Heriansyah; Arif Nurwaskito; Suriyanto Bakri; Mubdiana Arifin (Universitas Muslim Indonesia, 2023)
Mining materials can be in the form of material (over-burden) and potentially contain sulfide minerals, the research location is a former iron ore mining, it is known that iron ore is an acid mine drainage forming material. This characterization test of acid mine drainage forming samples can be used as a consideration in environmental management design to minimize unwanted environmental impacts. This study aims to analyze the mineralogical content of rocks, the potential of rocks as acid mine drainage formers, and determine management methods if the potential for acid mine drainage is indicated. The samples used were 5 rock samples in the pit and disposal, using petrography, mineragraphy, and XRD mineralogy analysis to determine the mineral composition contained, and kinetic testing to determine the reaction rate of acid mine drainage formation. The results of the analysis obtained the composition of metal minerals contained in samples 4 and 5, namely pyrite, hematite, magnetite, and geotite. Whereas in samples 1, 2, and 3 not enough metal minerals were detected. The results of the kinetic test analysis produce accurate data for samples 4 and 5 which have low or acidic pH values 6. So it can be concluded that the potential for the formation of acid mine drainage is found in samples in the disposal, namely iron ore with a low pH value 6 (acidic), methods that can be used in the process of preventing and controlling acid mine drainage can be done passively by using NAF material to stockpile polluted PAF material.